Responsabilidade pelos danos causados pela efetivação de tutelas de urgência quando do resultado desfavorável da demanda - Marques, Bruno Pereira (2015)
The analysis of liability for damage caused by the execution of injunctive relief when the demand is dismissed necessarily imposes an initial analysis from the constitutional perspective. Observes, therefore, that such a perspective illustrates the injunctive relief idea, in the effectiveness of optics, and liability from the perspective of heritage preservation and sharing of risks. The liability is based also on your infra-constitutional aspect, in a wide damage repairability, based on the prohibition to cause damage to third parties. Where once had its focus on punishing the conduct which cause damage, strongly highlighted by the adoption of "filters", modernly has been gaining strength the focus aimed at damage repair itself considered restricting limitation resulting from the exacerbation of their assumptions (especially fault and causation). In turn and in spite of the similarity, the procedural liability gains autonomy from civil liabilityhaving own assumptions, although similar, being remarkable that its effects are felt in the procedural relationship. The injunctive relief appear as instrument at the service of his postulant in the "fight" against the deleterious effects of time, the most prominent form of differentiated legal protection granted based on summary judgments about the authorizers requirements of its concession (the risk of the delay) and the adopted technique of differentiation of ordinary guardianship (restriction of cognition). However, if on the one hand provides a benefit to whom postulates, it imposes to the defendant the possibility of suffer damage. In this sense, the procedural risk theory appears as the main support of the objective procedural responsibility in case of rejection of the demand, being possible also invoke the general rule of objective civil liability with regard to activities involving risks to third parties, as well as highlight the similarity among injunctive relief execution and the provisional enforcement and the need of similar treatment concerning the liability.